Analysis of the environmental sustainability of buildings using BIM (Building Information Modeling) methodology (2017)
(Eng) The construction sector is currently facing two important challenges with regard to minimizing the environmental impact of its projects and improving the efficacy of the construction processes, providing clients with adequate solutions that meet their requirements. In response to the need to complete projects that satisfy environmental requirements, methodologies for project integration known as Building Information Modeling (BIM) have emerged in recent years. These methodologies enable the generation of digital models that contribute to minimizing errors and to the early detection of incompatibilities, and they allow participants to work in an integrated manner. These methodologies show notable synergy with sustainability, as digital modeling provides information about the performance of projects during their useful life, enabling the analysis of different options to minimize their environmental impact. The objective of the present study is to examine the performance of a construction project in Colombia in terms of sustainability by using a BIM platform to determine the electrical energy consumption, the carbon footprint of materials, and the total energy incorporated into the project using simulations. In addition, the generation of alternative designs and the analysis of the results will be performed considering the economic viability of the proposed scenarios.